A network pharmacology approach to investigate the mechanism of Shuxuening injection in the treatment of ischemic stroke. (15th July 2020) - Cui, Qian; Zhang, Yu-liang; Ma, Yu-hui; Yu, Hao-yu; Zhao, Xin-zhe; Zhang, Li-hui; Ge, Shao-qin; Zhang, Guo-wei; Qin, Xiu-de
Abstract: Ethnopharmacological relevance: Shuxuening injection (SXNI), a popular herbal medicine, is an extract of Ginkgo biloba leaves (GBE), and is used to treat ischemic stroke (IS) in China. However, its specific active ingredients and molecular mechanisms in IS remain unclear. Aim of the study: The purpose of the research is to identify the main active ingredients in GBE and explore its molecular mechanisms in the treatment of IS. Materials and methods: The main active components of GBE were discerned through the Traditional Chinese Medicine Systems Pharmacology Database and Analysis (TCMSP), Traditional Chinese Medicine Integrated Database (TCMID), Bioinformatics Analysis Tool for Molecular Mechanism of Traditional Chinese Medicine (BATMAN-TCM) database, and absorption, distribution, metabolism and excretion (ADME) analysis. The targets related to IS were obtained using Genecards, Online Mendelian Inheritance in Man (OMIM), Therapeutic Target Database (TTD), and Disgenet. We discovered an intersection of genes. Subsequently, protein-protein interaction (PPI) networks were constructed with Cytoscape 3.7.1 and the String database. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to analyze the intersection of targets via the Database for Annotation, Visualization, and Integrated Discovery (DAVID) 6.8. Built on the above analysis, we made a Compound-Target-Pathway (C-T-P) network. Autodock Vina was used for molecular docking analysis. Maestro 11.9 was used to calculate the root-mean-square deviation (RMSD). Animal experiments were performed to verify the core targets. Triphenyl tetrazolium chloride (TTC) staining was used to calculate the infarct volume in rats. Hematoxylin-eosin (HE) staining was employed to observe the morphology of hippocampal neuron cells. RT-qPCR was applied to detect relative mRNA levels, and protein expression was determined using Western blotting. Results: Molecular docking showed that PTGS2, NOS3 and CASP3 docked with small molecule compounds. According to RT-qPCR and Western blotting, mRNA and protein expression of PTGS2 and CASP3 were up-regulated (P < 0.05), and mRNA and protein levels of NOS3 were down-regulated (P < 0.05). Conclusions: SXNI can treat IS through multiple targets and routes, and reduce the apoptosis of neuron cells in brain tissue by inhibiting inflammation and regulating the level of oxidative stress, thereby protecting rats brain tissue. Graphical abstract: Image 1